2006
DOI: 10.1111/j.1439-0264.2006.00689.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Localization of Insulin‐Like Growth Factor‐I Receptor (IGF‐IR) in the Developing and Mature Rat Testes

Abstract: It has been suggested that insulin-like growth factor-I (IGF-I) plays an important role in the regulation of spermatogenesis in the testes. Its signal is mediated predominantly by the IGF-I receptor (IGF-IR). Signalling through IGF-IR has been shown to have a potent survival function. IGF-IR, a transmembrane tyrosine kinase, is widely expressed across many cell types. In this study, we demonstrated the distribution of IGF-IR in testes of differently aged rats. Anti-IGF-IR is a rabbit polyclonal antibody raised… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 46 publications
2
11
0
Order By: Relevance
“…In this present study, no IGF‐IR immunolabelling in Sertoli cells was observed at any age group, suggesting the IGF‐I system may not have a role in Sertoli cell function. A similar result showing the lack of IGF‐IR presence in Sertoli cells was previously reported in rats (Yagci and Zik 2006). In humans, the IGF‐IR immunolabelling of Sertoli cells was less intense than in Leydig cells (Vannelli et al.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…In this present study, no IGF‐IR immunolabelling in Sertoli cells was observed at any age group, suggesting the IGF‐I system may not have a role in Sertoli cell function. A similar result showing the lack of IGF‐IR presence in Sertoli cells was previously reported in rats (Yagci and Zik 2006). In humans, the IGF‐IR immunolabelling of Sertoli cells was less intense than in Leydig cells (Vannelli et al.…”
Section: Discussionsupporting
confidence: 89%
“…The IGF‐IR labelling in Leydig cells was moderate in pubertal stallion, but became very strong in post‐pubertal stallions. The same pattern of IGF‐IR immunolabelling in the Leydig cells was reported in rats (Yagci and Zik 2006). This age‐dependent change in the immunolabelling appears to be because of the age‐associated modification in composition of Leydig cells.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations